Thyroid storm-induced acute liver dysfunction and portal hypertension in a patient with Graves' disease: a case report - Mouna Medhioub; Amal Khsiba; Moufida Mahmoudi; Asma Ben Mohamed; Manel Yakoubi; Emna Haouet; Lamine Hamzaoui (Future Science OA, 2024)
Thyroid storm is a life-threatening condition associated with multiorgan dysfunction and decompensation. We report the case of a 41-year-old woman having Graves' disease presented with thyroid storm complicated with liver dysfunction and portal hypertension in the absence of congestive heart failure or known liver disease. After successful therapeutic management, all biological, clinical and morphological abnormalities regressed.